Cross-Reactivity of IgG Antibodies and Virus Neutralization in mRNA-Vaccinated People Against Wild-Type SARS-CoV-2 and the Five Most Common SARS-CoV-2 Variants of Concern - Schwarze, Mandy; Krizsan, Andor; Brakel, Alexandra; Pohl, Fabian; Volke, Daniela; Hoffmann, Ralf (Frontiers in Immunology, 2022)
The rapid development, approval, and production of vaccines against the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) within less than one year after the first reports of a new infectious disease was a real game changer providing a 80-90% efficacy in preventing severe etiopathologies of the coronavirus disease 2019 (COVID-19). These vaccines induce an immune response against the SARS-CoV-2 spike (S-) protein located on the surface of the virus particle. Antibodies (Abs) recognizing the S-protein can inhibit binding of the virus via the S-protein to the angiotensin converting enzyme-2 (ACE-2) receptor expressed on different human cells, especially when these Abs bind to the interaction site, the so-called receptor binding domain (RBD). We have expressed the RBDs of wild type SARS-CoV-2 and five variants of concern (VOCs) to test the immune response in persons before vaccination with mRNA vaccines BNT162b2 and mRNA-1273 and after up to three vaccinations using in-house ELISA and inhibition assays. The methods of both assays are provided. Both vaccines initiated similarly high IgG-titers after two vaccinations against the wild type and even two VOC-RBDs (alpha and delta) and strongly inhibited the corresponding RBD-ACE-2 binding. The IgG titers and inhibition of ACE-2 binding was lower for beta and gamma RBDs and much lower for omicron RBD. The third vaccination after six months strongly increased both the IgG titers and the neutralizing effect against all variants, especially for omicron leading to a 63±13% neutralization potential. Importantly, neutralization linearly increased with the IgG titers.